Alegrias e tristezas nas intera????es escolares: um estudo entre a ??tica de Espinosa e o interacionismo de Vigotski - Nakao, Am??lia Rosa Leite Moura (2016)
This research addresses one of the problems that most affects the process of teaching and learning in public schools in the Distrito Federal, and refers to the large number of departures of teachers from the classroom. In this sense, the objective was to discuss what has provoked this absence justified and which presents as psychological and emotional problems, depression, panic attacks and other phobias. Whereas the school is permeated by cultural, social aspects, values, meanings and emotional and sensitive relationships, sought to highlight intersubjective factors and objectives in school that interfere negatively experienced in pedagogical and social experience of the teachers. For such was used a participatory intervention, through the focus group, with the description of the professional experience of four educators of elementary and secondary education, with accounts of social interactions present in the school environment. The theoretical foundation if program mainly in Spinoza and the ethics of interactionism Vygotsky, who has guided the identification of factors that contribute to the removal of classroom teachers, as well as promoted the construction of suggestions aiming to collaborate with the accompaniment of those teachers, in order to intervene positively in the process of prevention and recovery from illness of psychoemotional order. Among the factors most discussed and reported by educators, the absence of an institutional work of listening and, combined with the lack of appreciation, it makes the point that the educators become incapacitated and unprepared to face a school complex and permeated everyday life due to lack of logistics. It was noted that the lack of ethics and of the affections has interfered negatively, since they feel unmotivated under the intellectual and emotional point of view to perform activities that could make a difference with your students.